Pengaruh Circuit Training Terhadap Kecepatan dan Kelincahan Pada Pemain Beka United Futsal Academy - Devi, Vanda Umaya, Sugiono, S.Fis., M.H (Kes) (2017)
Background : A futsal player must have speed and agility to catch the ball, seize and dribble up to the opponent's goal. To improve the speed and agility in futsal players will be given exercises is circuit training. Objective : To know the effect of circuit training for speed and agility on beka united futsal academy player's. Methods : This type of research in this study is a quasi experimental with pre and post test approach with non-equivalent control design . The sampling technique is purposive sampling with inclusion and exclusion criteria. Speed measurement using run 50 yard and agility measurement using illinois agility test. The data analysis using paired sample t-test and independent sample t-test, p-value < 0,05 there is the influence or p value > 0,05 there is not the influence. Result : Statistical analysis using paired sample t-test on the obtained results the effect of circuit training to speed with p value 0,000 (<0,05) and for agility with p value 0,000 (<0,05). Then to test different effect between the experimental group and the control group for the results obtained speed with p value 0,02 < (0,05) and for agility with p value 0,031 < (0,05) which means there are significant differences between experimental group and control groups. Conclusions : There is influence of circuit training for speed and agility on beka united futsal academy player's.